2013
DOI: 10.1093/qjmed/hct003
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tuberculosis: a retrospective review of cases presenting to a UK district hospital

Abstract: ATB is a diagnostic challenge, especially in absence of lung involvement. It mimics other diseases and clinical presentation is usually non-specific, which may lead to diagnostic delay and development of complications. Extreme vigilance should be used when dealing with unexplained abdominal symptoms to ensure timely diagnosis of ATB. Early diagnosis with early anti-tuberculous therapy and surgical treatment are essential to ensure as positive an outcome as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 9 publications
5
49
0
1
Order By: Relevance
“…(12) This is consistent with the increased health seeking behaviour amongst males in our country. There were mostly young adults as seen in most studies (10,11,13).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…(12) This is consistent with the increased health seeking behaviour amongst males in our country. There were mostly young adults as seen in most studies (10,11,13).…”
Section: Discussionmentioning
confidence: 95%
“…This is similar to other studies. (9)(10)(11) However some European studies found equal preponderance among both genders. (12) This is consistent with the increased health seeking behaviour amongst males in our country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis of abdominal TB in children is challenging due to nonspecific clinical features depending on host factors such as age and immunological status; and in most cases, pulmonary TB is absent making it difficult to establish the diagnosis (6,(14)(15)(16)(17)(18). Less than half of the patients can be diagnosed with abdominal TB when the only clinical presentation is abdominal complaint such as pain (3).…”
Section: Introductionmentioning
confidence: 99%